2009
DOI: 10.1124/jpet.109.153023
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1 Receptor Induces Cytosolic Calcium Increase and Aquaporin Translocation in Human Salivary Gland Cells

Abstract: One of the common side effects of antihistamine medicines is xerostomia (dry mouth). The current consensus is that antihistamine-induced xerostomia comes from an antimuscarinic effect. Although the effect of antihistamines on salivary secretion is both obvious and significant, the cellular mechanism whereby this happens is still unclear because of the lack of knowledge of histamine signaling in human salivary glands. Here, we have studied histamine receptors and the effect of antihistamines on human submandibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
1
31
0
2
Order By: Relevance
“…In nuclei, AQP5 may be triggered to facilitate water transport across the nuclear membrane. Enhancement of [Ca 2+ ]i-induced trafficking of AQP5 is observed in eccrine sweat glands [18], submandibular glands [17,61] and human salivary gland cells [62]. The enhancement of c-APM-induced trafficking of AQP5 is seen in Brunner's glands [63,64] and lung epithelial cells [65].…”
Section: Closedmentioning
confidence: 90%
“…In nuclei, AQP5 may be triggered to facilitate water transport across the nuclear membrane. Enhancement of [Ca 2+ ]i-induced trafficking of AQP5 is observed in eccrine sweat glands [18], submandibular glands [17,61] and human salivary gland cells [62]. The enhancement of c-APM-induced trafficking of AQP5 is seen in Brunner's glands [63,64] and lung epithelial cells [65].…”
Section: Closedmentioning
confidence: 90%
“…Furthermore, previous studies have demonstrated the presence of histamine H1 and H2 receptor subtypes in rat SMG [31,48,49]. Histamine treatment also induces the translocation of aquaporin-5, which modulates water secretion to produce primary saliva, to the plasma membrane in human SMG cells through the histamine H1 receptor [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have demonstrated the presence of histamine H1 and H2 receptor subtypes in rat SMG [31,48,49]. Histamine treatment also induces the translocation of aquaporin-5, which modulates water secretion to produce primary saliva, to the plasma membrane in human SMG cells through the histamine H1 receptor [31]. In this regard, histamine H1 receptor antagonists prescribed for allergic reactions are reported to cause xerostomia (dry mouth), which is a pathological condition characterized by decreased salivary secretion [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear evidence by fluorescence microscopy method also showed the up-regulation effect of DP on AQP5 in vitro test (Fig.2). Probably, such neural modulation as the role DP might play as the agonist of muscarinic acetylcholine receptor to increase the expression of AQP5 (Kim, Park et al 2009). …”
mentioning
confidence: 98%